Assessing the environmental footprint of recycled plastic pellets: A life-cycle assessment perspective - Junaid Saleem (14670322) (2023)
Plastic production has significant environmental impacts, including water pollution, global warming, resource depletion, and microplastic pollution. To address this, it is crucial to reduce plastic production and find more sustainable alternatives. While recycling plastic waste can help mitigate environmental impacts, it requires careful assessment. This study evaluates the environmental impact of producing polymer pellets from recycled polyolefin-based plastic waste using life-cycle assessment with Gabi software. Xylene is used as a solvent and later recovered. Two scenarios with different xylene recovery levels are assessed. The results show that 100% xylene recovery consumes more energy but reduces the carbon footprint. Additionally, carbon emissions during pellet production from plastic waste are 22.6%, and other impacts are in the range of 11%–40% lower compared to virgin polypropylene PP. The use of solar photovoltaic electricity demonstrates potential in reducing overall environmental impacts, except for human toxicity. The carbon emissions are found to be 41.8% lower than that of virgin PP. The study emphasizes the importance of sustainable techniques in mitigating plastic waste effects and offers insights for policymakers and stakeholders interested in a circular economy. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2023.103289